Decision Support System Using Simple Additive Weighting (SAW) Method For Teacher Performance Assessment At SMP Ki Hajar Dewantoro: Sistem Pendukung Keputusan Menggunakan Metode Simple Additive Weighting (SAW) Untuk Penilaian Kinerja Guru Di SMP Ki Hajar Dewantoro - Rahmat Fajar; Anita Diana; Rusdah Rusdah; Yuliazmi Yuliazmi; Dwi Achadiani (Universitas Singaperbangsa Karawang, 2023)
The teacher is a qualified educator who is responsible for teaching, and has a function and role in educating the nation's daily life. So that the roles and responsibilities in the teacher's functional position to be done according to the applicable regulations, a teacher's work assessment is needed which can guarantee a quality learning process at SMP Ki Hajar Dewantoro. In the process of selecting the best teacher for SMP Ki Hajar Dewantoro, there was already a weighting of the assessment criteria. However, a number of challenges arise, including the procedure of assessing teacher performance still using conventional methods with paper and ordinary calculations, so that the results of the assessment can occur errors or are inaccurate, and take a little time. Teacher ratings are also inaccurate and subjective, making it difficult to determine the best teacher. In addition, the decree for the best teacher is not well preserved. Therefore, a Decision Support System (DSS) is needed to recommend the best teacher using thethe Technique known as SAW (Simple Additive Weighting). The SAW approach was chosen due to it uses a method of ranking to choose the best option from a number of others and then determines the preference weight value for each option, specifically, the teacher with the highest rank according to the specified standards. due to the fact that it is based on the weight value of the existing criteria, this method will make the assessment faster, it can provide the best alternative teacher ranking. With the results of these rankings, it can simplify and assist the school in accelerating the assessment of teacher performance, so that more accurate results will be obtained as a decision tool.